2017
DOI: 10.1039/c6nj03922g
|View full text |Cite
|
Sign up to set email alerts
|

Controllable TiO2 heterostructure with carbon hybrid materials for enhanced photoelectrochemical performance

Abstract: A TiO2/RGO/C3N4 heterostructure has been successfully designed and fabricated, and the narrow bandgap and conductivity of RGO and C3N4 could be beneficial for the generation and separation of photocharges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
3
0
2
Order By: Relevance
“…Figure a shows the procedure for synthesis of PDA/Bi‐AgIn 5 S 8 /TiO 2 heterostructure. The vertically aligned TiO 2 nanowires (TiO 2 NWs) were grown on the FTO substrate by a hydrothermal method, and then Bi‐AgIn 5 S 8 film was deposited on the TiO 2 NWs . Finally, the PDA was introduced onto the surface of Bi‐AgIn 5 S 8 film through spontaneous polymerization of dopamine through chemical bath deposition (CBD) .…”
Section: Resultsmentioning
confidence: 99%
“…Figure a shows the procedure for synthesis of PDA/Bi‐AgIn 5 S 8 /TiO 2 heterostructure. The vertically aligned TiO 2 nanowires (TiO 2 NWs) were grown on the FTO substrate by a hydrothermal method, and then Bi‐AgIn 5 S 8 film was deposited on the TiO 2 NWs . Finally, the PDA was introduced onto the surface of Bi‐AgIn 5 S 8 film through spontaneous polymerization of dopamine through chemical bath deposition (CBD) .…”
Section: Resultsmentioning
confidence: 99%
“…synthesized a2 D in-plane WC/graphene heterostructure.T his structure ensured the electrons transfer more efficiently between graphene and WC. [171][172][173][174] Consequently,t he HER performance was improved with ar emarkably lower Tafel slope of 38 mV dec À1 .I na ddition to the 2D structure,R amakrishna et al reported a3 Dn anocomposite architecture of cobalt disulfide/reduced graphene oxide/carbon nanotubes (CoS 2 / RGO/CNTs) as the HER catalyst, [32] where the 2D RGO and 1D CNTs could construct a3 Df ramework for electron transportation and the anchoring of CoS 2 nanoparticles. Consequently,t his synergistic effect reduced the Tafel slope to 51 mV dec À1 .T his result is better than most non-noblemetal electrocatalysts.…”
Section: Heterostructurementioning
confidence: 99%
“…synthesized a 2D in‐plane WC/graphene heterostructure. This structure ensured the electrons transfer more efficiently between graphene and WC . Consequently, the HER performance was improved with a remarkably lower Tafel slope of 38 mV dec −1 .…”
Section: Heterostructurementioning
confidence: 99%
“…[159,168,169] Statt der Herstellung gestapelter und verdichteter Heterostrukturen synthetisierten Fu et al beispielsweise eine 2D-In-Plane-WC/ Graphen-Heterostruktur.D iese bewirkte einen effizienteren Elektronentransfer zwischen Graphen und WC. [171][172][173][174] Als Folge wurde die HER-Leistungsfähigkeit verbessert, mit einer bemerkenswert niedrigen Tafel-Steigung von 38 mV dec À1 .Z usätzlich zur 2D-Struktur berichteten Ramakrishna et al von einer 3D-Nanokomposit-Architektura us Cobaltdisulfid, reduziertem Graphenoxid und Kohlenstoff-Nanorçhren (CoS 2 /RGO/CNTs) als HER-Katalysator, [32] bei der 2D-RGO und 1D-CNTs ein 3D-Gerüst fürE lektronentransport und die Verankerung von CoS 2 -Nanopartikeln bildeten. Dieser synergetische Effekt verringerte die Tafel-Steigung auf 51 mV dec À1 ,ein Wert, der besser ist als bei den meisten Nichtedelmetall-Elektrokatalysatoren.…”
Section: Heterostrukturunclassified
“…beispielsweise eine 2D‐In‐Plane‐WC/Graphen‐Heterostruktur. Diese bewirkte einen effizienteren Elektronentransfer zwischen Graphen und WC . Als Folge wurde die HER‐Leistungsfähigkeit verbessert, mit einer bemerkenswert niedrigen Tafel‐Steigung von 38 mV dec −1 .…”
Section: Heterostrukturunclassified